Deteksi Dini Gangguan Pertumbuhan dan Perkembangan Anak - Atien Nur Chamidah (JPK (Jurnal Pendidikan Khusus), 2009)
Growth and development process can show the quality of child. Growth and development process which started from prenatal phase is a result of interaction between genetic factor and environment factor. The process has faster improvement on early age, 0-5 years old which is called "Golden Age" phase. We have to make accurate attention on golden age phase because it is an important phase on children growth and development. Early detection is important to find problems of children growth and development. If we can detect the problems early we can make a precious intervention to prevent permanent disability. Early detection of children growth and development problems consist of physical, motor development, emotion and behavior  assessment.